Margaret Conrad: The Making of a Political Historian and Commentator - Campbell, Gail (Atlantis, 2010)
Margaret Conrad started out as a political historian; her first major work was a political biography. Yet even her earliest work was non-traditional and innovative. Her dynamism and engagement with political history make her one of Canada's most distinguished historians, astute commentators and thoughtful critics of current Canadian politics.